Mobile applications as a strategy to support parents in the care of newborns: a scoping review - Araujo, Juliane Pagliari; Gallo, Adriana Martins; de Lima Parada, Cristina Maria Garcia [UNESP]; Marcon, Sonia Silva; Ferrari, Rosângela Aparecida Pimenta; da Fonseca Pinto, Keli Regiane Tomeleri; Zani, Adriana Valongo (FapUNIFESP (SciELO), 2023)
Objective: To map and describe studies available in the literature about mobile applications to support parents in newborn care and data from applications accessible in online stores. Method: This is a scoping review following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines. The searches were carried out in theses and dissertations databases and portals, in September 2021, and articles, theses, and dissertations were included. An independent search was performed in online stores of applications for operating systems Android and iOS, in October and December 2021, and applications with content to support parents of newborns were selected. Results: A total of 5,238 studies and 757 applications were found, and of these, 16 and 150, respectively, composed the sample. The topics discussed in the studies were: care, breastfeeding, fever, identification of neonatal diseases, child growth and development. In the applications, the themes found were care, breastfeeding, growth, immunization, development, sleep, tips, and guidelines. Conclusion: Applications are important support tools for parents, as they are an innovative means and accessible to a large part of the population.
Aplicaciones móviles como estrategia de apoyo a los padres en el cuidado del recién nacido: revisión de alcance
Aplicativos móveis como estratégia de apoio a pais no cuidado ao recém-nascido: revisão de escopo
Keywords: Access to Information; Infant; Mobile Applications; Newborn; Parents; Smartphone